(untitled) (Veterinary Science, 2023)
Canine zoonotic parasites have been recognized as a significant public health problem especially in developing countries with vulnerable socio-environmental conditions. In the context of “One Health” the aim of this work was to assess the animal domain by the evaluation of canine zoonotic enteroparasites associated to a Parasite Vulnerability Index (PVI) in peripheral (PC) and urban communities (UC) from Mar del Plata city. The PVI was elaborated in a previous work as a vulnerability indicator of parasite diseases, in relation to socio-environmental conditions surveyed in the communities about the next dimensions: house, sanitation, hygiene, education and work. A coproparasitological study was performed to establish the presence and the richness of canine parasites in the environment in both communities. The PC evidenced homes with a higher mean number of canine fecal samples (CFS) with parasites than the UC, showing also the highest parasite specific richness with helminths and protozoan. Frequencies of Ancylostomids, Capillariids and Toxocara canis were higher in the PC, but Trichuris vulpis frequencies and the positive coproantigen test to detect Echinococcus granulosus, were similar between communities. The PC evidenced association to variables related to dogs’ ownership (absence of veterinary attention and not adequate deworming), with the presence of CFS with parasites and the positive coproantigen test. Families with medium and high PVI from the PC evidenced a strong association with the presence of CFS with parasites and also with high parasitic richness, while families from the UC with low PVI evidenced CFS without parasites. These results revealed a vulnerable scenario for the permanence and the transmission of canine zoonotic parasites in most families from the PC, highlighting the value of the socio-environmental features as predictors of parasitoses.